How do nations around the world navigate the digitalization of vocational education policies? - Diao, Junfeng; Tang, Xiaoqi; Ding, Xu (Education and information technologies, 2025)
This study provides a comprehensive analysis of vocational education digitalization policies across China, Australia, Japan, Germany, and the UK. It utilizes a multi-dimensional framework to assess policy subjects, themes and instruments. The findings highlight multi-stakeholder involvement and varying national approaches. A collective commitment to enhancing digital skills and aligning vocational education with industry requirements is evident, though specific priorities vary by country. There is a significant focus on supply-side policy instruments often at the expense of demand-side considerations. Common challenges include digital infrastructure disparity and the complexity of stakeholder collaboration. To address these, the study recommends enhancing collaboration mechanisms among diverse subjects, improving resource allocation, and balancing market-driven and government-led initiatives. Further, it suggests optimizing policy content, and enhancing policy instrument synergy and alignment with national and international contexts.